2017
DOI: 10.32404/rean.v4i3.1611
|View full text |Cite
|
Sign up to set email alerts
|

Embalagem E Tratamento Hidrotérmico Na Manutenção Da Qualidade Pós-Colheita De Jambu

Abstract: O jambu também conhecido como agrião bravo e jambu pequeno é uma hortaliça folhosa que apresenta elevada perecibilidade após a colheita, observada pela rápida deterioração e intensa perda de água. Desta forma, o presente trabalho tem por objetivo avaliar a conservação pós-colheita do jambu pelo uso do hidroresfriamento e do acondicionamento em diferentes embalagens. O experimento foi conduzido em um delineamento experimental inteiramente casualizado em arranjo fatorial 5x5, sendo cinco tratamentos e cinco temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…In this context, Oliveira et al (2017) evaluating the postharvest quality in the conservation of jambu according to the type of packaging and hydrothermal treatment, also observed that the reduction of the jambu temperature, through cooling, as well as the use of plastic packaging can prolong the shelf life of this hardwood. They reached this conclusion when they evaluated these treatments and verified that these, individual or associated, caused the plant to present less water loss at the end of storage, which was 12 days.…”
Section: Resultsmentioning
confidence: 96%
“…In this context, Oliveira et al (2017) evaluating the postharvest quality in the conservation of jambu according to the type of packaging and hydrothermal treatment, also observed that the reduction of the jambu temperature, through cooling, as well as the use of plastic packaging can prolong the shelf life of this hardwood. They reached this conclusion when they evaluated these treatments and verified that these, individual or associated, caused the plant to present less water loss at the end of storage, which was 12 days.…”
Section: Resultsmentioning
confidence: 96%
“…A perda de massa em produtos hortícolas consiste na redução do peso fresco do produto ao longo do tempo e está diretamente relacionada à movimentação de água no produto após a colheita, determinadas pela perda de água por transpiração. Esse intenso processo de transpiração ocasiona um déficit e o produto perde água para o ambiente iniciando um estresse hídrico que tem por características a perda de turgidez e a redução do peso fresco (OLIVEIRA et al, 2017;SANCHES et al, 2017).…”
Section: Resultsunclassified
“…The subjective assessment provides information on the physical quality of leafy vegetables because by being chosen by consumers, they are judging in some way whether the overall appearance of the product meets their expectations and requirements (Oliveira et al, 2017). The appearance attribute is of fundamental importance for marketing, as the consumer makes the purchase decision based on the physical aspect of arugula leaves.…”
Section: Resultsmentioning
confidence: 99%